Text data labeling method and device, computer device and computer readable storage medium - WANG ZHICHAO; HE ZHONGHE; ZUO LINGFENG; HE ZIYANG (2020)
The invention is applicable to the technical field of the Internet, and provides a text data labeling method and device, a computer device and a computer readable storage medium, the method comprisesthe following steps: obtaining a webpage text containing a subject-guest keyword pair, segmenting the webpage text according to a paragraph structure, and performing clause processing to obtain a to-be-processed statement; carrying out subject-subject keyword pair, regular expression and exhaustion keyword matching on the to-be-processed statement, and when at least one of the matching succeeds, taking the to-be-processed statement as a candidate statement, and storing the candidate statement into a list set; circularly traversing the list set, processing candidate sentences in the list set, selecting sentences meeting preset conditions from the candidate sentences as valid sentences, and storing the valid sentences into a database; displaying valid statements. According to the text data annotation method provided